2015
DOI: 10.15252/emmm.201404062
|View full text |Cite
|
Sign up to set email alerts
|

In vivo generation of a mature and functional artificial skeletal muscle

Abstract: Extensive loss of skeletal muscle tissue results in mutilations and severe loss of function. In vitro-generated artificial muscles undergo necrosis when transplanted in vivo before host angiogenesis may provide oxygen for fibre survival. Here, we report a novel strategy based upon the use of mouse or human mesoangioblasts encapsulated inside PEG-fibrinogen hydrogel. Once engineered to express placental-derived growth factor, mesoangioblasts attract host vessels and nerves, contributing to in vivo survival and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 29 publications
2
93
0
Order By: Relevance
“…In vivo , these systems have been shown to enhance the contractile function of severely injured muscle tissue when myoblasts were co-delivered with IGF-1 to promote myogenesis and VEGF to promote angiogenesis [33,34]. The importance of concurrently promoting angiogenesis with cell delivery was also shown using delivery of mesoangioblasts expressing placental-derived growth factor (PIGF) inside a PEG-fibrinogen hydrogel; the expression of PIGF led to the formation of new blood vessels and nerves within the newly formed myofibers that were used to replace ablated muscle tissue [35]. In the absence of cues to actively promote angiogenesis, it has been demonstrated that cells delivered progressively in thin fibrin gel layers to a site of volumetric muscle loss allows for host angiogenesis in each new layer, enhancing the survival of the new tissue [36].…”
Section: Muscle Cells Combined With Biomaterialsmentioning
confidence: 99%
“…In vivo , these systems have been shown to enhance the contractile function of severely injured muscle tissue when myoblasts were co-delivered with IGF-1 to promote myogenesis and VEGF to promote angiogenesis [33,34]. The importance of concurrently promoting angiogenesis with cell delivery was also shown using delivery of mesoangioblasts expressing placental-derived growth factor (PIGF) inside a PEG-fibrinogen hydrogel; the expression of PIGF led to the formation of new blood vessels and nerves within the newly formed myofibers that were used to replace ablated muscle tissue [35]. In the absence of cues to actively promote angiogenesis, it has been demonstrated that cells delivered progressively in thin fibrin gel layers to a site of volumetric muscle loss allows for host angiogenesis in each new layer, enhancing the survival of the new tissue [36].…”
Section: Muscle Cells Combined With Biomaterialsmentioning
confidence: 99%
“…However, other applications that can potentially be applied more readily have been found, including tissue analogues that can be used for predicting the effect of new experimental drugs in models displaying muscular disorders. Furthermore, some studies employing biomaterial-based strategies have shed light upon the integration and function of regenerating muscle associated with the support of accelerated angiogenic and neurogenic responses [68,73].…”
Section: Hydrogels In Cell-based Therapiesmentioning
confidence: 99%
“…One such hydrogel is the PEGfibrinogen (PF), a photopolymerizable hydrogel, which enables the controlled and localized gelation when seeded with a cell suspension [118], both in vitro and also in vivo, particularly within a damaged muscle [65]. This semi-synthetic hydrogel has shown to support skeletal muscle survival, growth and maturation [68]. These materials are capable of supporting cell growth and undergoing proteolytic degradation via their biological domains while still providing robust mechanical properties emanating from their synthetic components [106].…”
Section: Hydrogel Biomaterialsmentioning
confidence: 99%
“…The implant was able to mature into artificial, functional skeletal muscle fibers in mice. Importantly, the cells were engineered to overexpress placental-derived growth factor, and the implant was successful with both murine and human mesoangioblasts [52]. With regard to the heart, myogenic mesoangioblasts [53] or pericytes [54] have been recently isolated also from the cardiac muscle, although their bench-to-bedside progression appears slower as compared to aforementioned cell systems.…”
Section: Artificial Tools To Regulate Mirsmentioning
confidence: 99%